The Implementation of the UMMI Method in Improving Quranic Reading at RA Adz Dzikra Ishhaarul Jannah - Selvia, Selvia; Andre, Lesis; Mirdad, Jamal; Rina, Rina (The Future of Education Journal, 2025)
Early Quranic education plays a crucial role in shaping a child's character and spirituality. At the Raudhatul Athfal (RA) level, introducing the Quran isn't just about memorization; it's about building a foundational understanding through methods that are easy, enjoyable, and effective. However, in reality, many children in RA still face challenges in reading the Quran with proper tartil (rhythmic and melodic recitation) and accuracy. This research aims to demonstrate that the Ummi Method offers an innovative solution with its "heart-to-heart" approach. The study's findings indicate that the implementation of the Ummi Method is systematically carried out in five core stages: opening, memorization, classical demonstration, evaluation, and closing. Based on student evaluation data, there was a significant improvement in Quran reading ability, shifting from 60% in the "sufficient" category to 85% in the "good" category after the Ummi Method was applied for one semester. This method also successfully fostered a love for learning and a sense of affection for the Quran in children from an early age.